Meningkatkan Ketrampilan Berfikir Tingkat Tinggi (HOTS) Dan Keterlibatan Mahasiswa Dalam Proses Pembelajaran Pendidikan Pancasila - Agus Widodo; Zainal Afandi; Suratman Suratman; Nursalim Nursalim; Etty Andyastuti; Septiana Septiana (University of Muhammadiyah Malang, 2023)
Higher Order Thinking Skills (HOTS) as an essential requirement in facing the challenges of chapter 21. This research aims to increase HOTS and student involvement in the learning process. The Socratic Method (Socrated Method) prioritizes in-depth discussion or dialogue (deep dialoque), where learning (teacher/lecturer) conveys deep questions (deep quitning) encourages students to think at a higher level. The Socratic method also encourages students to be actively involved in the learning process. This classroom action research uses 3 (three) cycles of steps; 1) problem assistance, 2) action plan, 3) action evaluation. The subjects were 29 students who took Pancasila Education lectures. The results showed that after 3 (three) cycles of action, HOTS increased by 45%. While student involvement has increased by 59%. So it can be said that the Socratic method can increase HOTS and student involvement in the lecture process.